Plasmablastic Lymphoma Involving Kidney in an HIV Positive Patient: A Case Report with Review of the Literature - Sulav Sapkota (Indian Journal of Nephrology, 2021)
Plasmablastic lymphoma (PBL) is an aggressive lymphoma commonly associated with HIV infection. It most commonly presents in the oral cavity and rarely involves the kidney. Herein, we report a case of HIV positive male with renal involvement of PBL. The patient presented with unilateral severe hydronephrosis with unaltered renal functions. Despite aggressive management, there was an early relapse and the patient died within 2 years of the diagnosis. Despite the recent advances in the therapy of HIV-associated aggressive lymphomas, patients with PBL have a poor prognosis. Multimodal treatment with chemotherapy, newer targeted and biological agents, along with hematopoietic stem cell transplantation is essential for the treatment of PBL.